Battery systems engineering - Rahn, Christopher D. (Wiley, 2013)
A complete all-in-one reference on the important interdisciplinary topic of Battery Systems Engineering Focusing on the interdisciplinary area of battery systems engineering, this book provides the background, models, solution techniques, and systems theory that are necessary for the development of advanced battery management systems. It covers the topic from the perspective of basic electrochemistry as well as systems engineering topics and provides a basis for battery modeling for system engineering of electric and hybrid electric vehicle platforms. This original approach gives a useful overview for systems engineers in chemical, mechanical, electrical, or aerospace engineering who are interested in learning more about batteries and how to use them effectively. Chemists, material scientists, and mathematical modelers can also benefit from this book by learning how their expertise affects battery management.-Approaches a topic which has experienced phenomenal growth in recent years -Topics covered include: Electrochemistry; Governing Equations; Discretization Methods; System Response and Battery Management Systems -Include tables, illustrations, photographs, graphs, worked examples, homework problems, and references, to thoroughly illustrate key material -Ideal for engineers working in the mechanical, electrical, and chemical fields as well as graduate students in these areas A valuable resource for Scientists and Engineers working in the battery or electric vehicle industries, Graduate students in mechanical engineering, electrical engineering, chemical engineering.